Therapies for people hospitalized with COVID-19 and alignment with national clinical guidelines in a large hospital, Almaty, Kazakhstan, 2020–2021 - Gazezova, Saya; Nabirova, Dilyara; Detmar, Ariana; Smagul, Manar; Kasabekova, Lena; Zikriyarova, Sanam; Horth, Roberta (Frontiers in Medicine, 2023)
Background Clinical practice guidelines were continually changing during the COVID-19 pandemic to reflect the best available evidence for a novel virus. In Kazakhstan, the national clinical guidelines for COVID-19 patient care were regularly modified and it was not known if and to what extent these guidelines were being followed in practice. Methods We conducted a sub-analysis of data collected from an observational study among people hospitalized with COVID-19 in a large infectious disease hospital in Almaty in four cross-sections of increased COVID-19 incidence: T1 (1 June–30 August 2020); T2 (1 October–31 December 2020); T3 (1 April–31 May 2021); and T4 (1 July–26 October 2021). Modifications to the national COVID-19 treatment guidelines were identified and clinical data were abstracted from electronic medical records. We assessed frequency of antibiotic, glucocorticoid, anticoagulant, and antiviral administered in each period and determined if these aligned with national clinical guidelines. We used multivariable logistic regression to compare practices across periods. Results Six modifications were made to national COVID-19 treatment guidelines during this study. Of 1,146 people hospitalized with COVID-19, 14% were in T1, 14% in T2, 22% in T3, and 50% in T4. Anticoagulant treatment was administered to 87% (range: 56%–95%), antibiotic treatment to 60% (range: 58%–64%), glucocorticoid to 55% (range: 43%–64%) and antiviral therapy 15% (range: 7%–22%). Majority of treatments were not aligned with national guidelines, including 98% of anticoagulant use, 95% of antibiotic use, 56% of glucocorticoid use, and 56% of antiviral use. There were no significant changes in practice following changes in guidelines for antibiotic use (64% in T1 to 58% in T2, p = 0.30). There was significant increase in use of anticoagulant (84% in T2 vs. 95% in T3, p < 0.01), glucocorticoid (43% in T2 vs. 64% in T3, p < 0.01), and antiviral treatment (7% in T3 vs. 15% in T4, p < 0.01) after guidelines updates. Conclusion The majority of treatments administered to people hospitalized with COVID-19 in four periods of high incidence in Almaty were not aligned with updated clinical guidelines. Antibiotic misuse was markedly high throughout. Increased awareness and training on clinical practice guidelines as updates are released may help improve adoption of evidence-based practices.